2022
DOI: 10.1177/11786469221128697
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Hesperidin Suppresses Lipopolysaccharide-Induced Inflammation in Male Mice

Abstract: Depressive disorders are partially attributed to chronic inflammation associated with the tryptophan (Trp)-kynurenine (Kyn) pathway. Recent evidence suggests that anti-inflammatory agents may reduce the risk of depression. The present study aimed to elucidate the potential of the citrus flavonoid hesperidin, which exhibits anti-inflammatory activity, in suppressing the Trp-Kyn pathway in the brain, using a lipopolysaccharide (LPS)-induced inflammation mouse model. Dietary hesperidin was found to suppress activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The lack of significant induction of KYN enzymes in the HPC may seem unexpected, but it actually fits with previous data reporting earlier peaks of expression, as well as different temporal expression patterns depending on the brain areas ( 62 , 68 ). Besides, several studies have confirmed that the increase in levels of KYN and its derivatives measured in the FCx and STR 24 h post-LPS was also significant in the HPC ( 13 , 63 , 68 , 85 ). Here, we showed that pretreatment with SE blunted the LPS-induced increase in expression of GTPCH1 in the STR and KYN enzymes in the FCx and STR.…”
Section: Discussionmentioning
confidence: 80%
“…The lack of significant induction of KYN enzymes in the HPC may seem unexpected, but it actually fits with previous data reporting earlier peaks of expression, as well as different temporal expression patterns depending on the brain areas ( 62 , 68 ). Besides, several studies have confirmed that the increase in levels of KYN and its derivatives measured in the FCx and STR 24 h post-LPS was also significant in the HPC ( 13 , 63 , 68 , 85 ). Here, we showed that pretreatment with SE blunted the LPS-induced increase in expression of GTPCH1 in the STR and KYN enzymes in the FCx and STR.…”
Section: Discussionmentioning
confidence: 80%
“…Among heavy metals, exposure of humans and experimental animals to lead (Pb 2+ ) resulted in lowered semen and sperm quality, inhibition of steroidogenesis in Leydig cells due to high levels of ROS, as well as changes in hormonal synthesis and regulation [ 35 , 36 , 37 , 84 , 85 ]. Hesperidin (HSD) is a natural antioxidant that has a wide range of pharmacological effects [ 62 , 63 ]. It has been suggested that HSD can counteract the molecular changes and toxicities brought on by toxic heavy metals via antioxidant, anti-inflammatory, and anti-apoptotic effects [ 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin (HSD; 3′,5,7-trihydroxy 4′-methoxyflavanone 7-rutinoside, hesperetin 7-rutinoside) is a flavanone glycoside found abundantly in citrus fruits (family Rutaceae ) [ 57 , 58 ] and is a prominent natural antioxidant known for its ability to reduce OS [ 59 , 60 ]. Moreover, numerous pharmacological activities of HSD have been reported, including, among others, anti-inflammatory, anticarcinogenic, and antimicrobial activities [ 61 , 62 , 63 ]. Notably, the pharmacological applications of HSD relied on its various advantages, including high safety profile, non-accumulative nature, and few adverse effects [ 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hesperidin derivatives have potent anti-inflammatory activity, as demonstrated in several animal models, as well as in humans [ 24 ]. The absence of an ortho- or para-diphenol moiety suggests that these compounds are ineffective in Nrf2 activation, while other molecular mechanisms explaining the anti-inflammatory activity have been proposed, including a strong inhibition of MAP kinases and expression of p-ERK and p38, thus reducing the levels of inflammatory cytokines [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%